Mandibular cortical bone evaluation on cone beam computed tomography images of patients with bisphosphonate related osteonecrosis of the jaws - Torres, Sandra; Chen, Curtis; Santos, Eduardo César Almada [UNESP]; Lee, Peggy P.; Hollender, Lars G. (My University, 2012)
Objectives The objective of this study was to develop a technique for detecting cortical bone dimensional changes in patients with bisphosphonate-related osteonecrosis of the jaw (BRONJ). Study Design Subjects with BRONJ who had cone-beam computed tomography imaging were selected, with age- and gender-matched controls. Mandibular cortical bone measurements to detect bisphosphonate-related cortical bone changes were made inferior to mental foramen, in 3 different ways: within a fixed sized rectangle, in a rectangle varying with the cortical height, and a ratio between area and height. Results Twelve BRONJ cases and 66 controls were evaluated. The cortical bone measurements were significantly higher in cases than controls for all 3 techniques. The bone measurements were strongly associated with BRONJ case status (odds ratio 3.36-7.84). The inter-rater reliability coefficients were high for all techniques (0.71-0.90). Conclusions Mandibular cortical bone measurement is a potentially useful tool in the detection of bone dimensional changes caused by bisphosphonates. Long-term administration of bisphosphonates (BPs) affects bone quality and metabolism following accumulation in bone.1 Since the first cases of bisphosphonate-related osteonecrosis of the jaw (BRONJ) were published in 2003,2 there has been a search for factors that can predict the onset of the condition. Oral and intravenous BPs reduce bone resorption, increase mineral content of bone, and alter bony architecture.3, 4, 5 and 6 Previous studies have demonstrated these changes both radiographically and following histologic analysis.1, 3, 7, 8, 9 and 10 The BP-related jaw changes may present radiological features, such as thickening of lamina dura and cortical borders, diffuse sclerosis, and narrowing of the mandibular canal3 and 11; however, oral radiographs of patients taking BPs do not consistently show radiographic changes to the jaws.11 and 12 The challenge is to find imaging tools that could improve the detection of changes in the bone associated with BP use. Various skeletal radiographic features associated with BRONJ in conventional periapical and panoramic radiographs, computed tomography, magnetic resonance imaging, and nuclear bone scanning have been described.3, 8, 9, 10 and 11 There has also been a search for BP-related quantitative methods for the evaluation of radiographic images, to avoid observer subjectivity in interpretation. Factors thought to be important include trabecular and cortical structure, and bone mineralization.4 Consequently, measurable bone data have been reported in subjects taking BPs through many techniques, including bone density, architecture, and cortical bone thickness.1, 4, 7 and 13 Trabecular microarchitecture of postmenopausal women has been evaluated with noninvasive techniques, such as high-resolution magnetic resonance images showing less deterioration of the bone 1 year after initiation of oral BP therapy.4 A decrease in bone turnover and a trend for an increase in the bone wall thickness has been detected by histomorphometry in subjects taking BPs.1 Alterations in the cortical structure of the second metacarpal have been detected in digital x-ray radiogrammetry of postmenopausal women treated with BPs.7 Mandibular cortical width may be measured on dental panoramic radiographs, and it has been suggested as a screening tool for referring patients for bone densitometry for osteoporosis investigation.14 and 15 Inhibition of the intracortical bone remodeling in the mandible of mice taking BPs has been reported.16 Thus, imaging evaluation of the mandibular cortical bone could be a biologically plausible way to detect BP bone alterations. Computed tomography can assess both cortical and trabecular bone characteristics. Cone-beam computed tomography (CBCT) can provide 3-dimensional information, while using lower doses and costing less than conventional CT. The CBCT images have been studied as a tool for the measurement of trabecular bone in patients with BRONJ.13 Therefore, cortical bone measurements on CBCT of the jaws might also help to understand bone changes in patients with BRONJ. There is no standard in quantifying dimensional changes of mandibular cortical bone. We explored several different approaches to take into consideration possible changes in length, area, and volume. These led to the 3 techniques developed in this study. This article reports a matched case-control study in which mandibular cortical bone was measured on CBCT images of subjects with BRONJ and controls. The aim of the study was to explore the usefulness of 3 techniques for detecting mandibular cortical bone dimensional changes caused by BP.